(untitled) (ModaPalavra e-periódico, 2021)
Sustainable fashion has been one of the most widely discussed topics in both academia and practitioner. The depletion of natural resources and the use of precarious labor promoted by the fashion industry demand urgent solutions for improvements in the sector. In addition to several concepts, new business models have emerged to integrate sustainability, however, a question arises: how is sustainability being incorporated into the business models present in sustainable fashion? Through a literature review, we sought to bring the main concepts of sustainable fashion and the existing business models in the area, namely: slow fashion, ethical fashion, eco-fashion, fair trade, zero-waste, circular economy, upcycling, recycling and shared economy / collaborative consumption. From this understanding, the eight sustainable business archetypes proposed by Bocken, et al. (2014) in order to verify which ones are applicable to the fashion industry.